Problems of human resources planning in Latin America and in the Mediterranean Regional Project countries: long-term forecasts of manpower requirements and educational policies; report on the Seminar held at Lima in March 1965 and complementary documents - Organisation for Economic Co-operation and Development ([Paris] : Organisation for Economic Co-operation and Development, 1967)
This seminar papers highlights basic problems associated with long-term forecasts on manpower, which was held in Lima in March 1965, by OECD and its Development Centre in cooperation with the Peruvian National Institute of Planning.
Bibliographical footnotes.
lje 21/01/19
Loans
Keywords: Manpower policy; Manpower policy; Labor supply; Labor supply